Nilai Multikultural Pada Masyarakat Sosio-Religius Pasca Konversi Agama Di Desa Lokapaksa Kecamatan Seririt Kabupaten Buleleng-Bali - Putra, Wayan Sunampan; Ni Made, Yunitha Asri Diantary (Widya Sandhi, 2024)
This research is one of the studies that focuses on Multicultural Values in Post-Religious Socio-Religious Communities in Lokapaksa Village, Seririt District, Buleleng Regency. Where there is a religious conversion and post-religious conversion does not cause conflict, people can even live in harmony. The purpose of this study is to explain how multicultural values are in post-religious conversion communities in Lokapaksa village. In explaining the formulation of the problem then using the functional structural theory. This type of research is qualitative research with primary and secondary data. Collecting data by observation, interviews, documentation, and literature study. Then the data is analyzed and presented. The data obtained is that the post-religious conversion of the Lokapaksa village community shows that there are multicultural values implemented by the people in the Lokapsa village such as openness values, democratic values, pluralism values, human values and nationalism values.